AN ANALYSIS OF PASSENGER PERCEPTIONS REGARDING AISLE AVOIDANCE BEHAVIORS ON PELITA AIR FLIGHTS CONCERNING SAFETY, SECURITY, AND COMFORT - Abdul Kudus Zaini; Julianti Puspa Hidayati; M. Zaenal Muttaqin (PT. Jurnal Center Indonesia Publisher, 2026)
Passenger movement within aircraft aisles is an essential activity during the flight process, particularly inside narrow-body aircraft where mobility remains restricted. Interactions between passengers frequently trigger avoidance behaviors that potentially influence perceptions of safety, security, and comfort during travel. Therefore, this study aims to analyze passenger perceptions of aisle avoidance on Pelita Air flights based on these three specific dimensions. Methodologically, the research utilizes a quantitative descriptive approach involving a five-point Likert scale questionnaire. Data were gathered from 350 respondents who previously utilized Pelita Air flight services. Furthermore, the analysis was conducted by calculating mean values to determine the categorization of respondent perceptions. Findings indicate that all variables fall within the “good” category. Specifically, the mean value for safety reached 4.098, security 4.099, and comfort 4.077. Effectively, these findings demonstrate that the avoidance process in the cabin aisle is perceived as safe, orderly, and sufficiently comfortable despite the limited space for movement. Importantly, this study contributes to the understanding of passenger behavior in confined cabin spaces and becomes valuable input for airlines to enhance the quality of cabin services.